A unique case of ovarian manifestation of systemic vasculitis that mimics ovarian cancer. - Bielejewska, Ada; Bociek, Arkadiusz; Bociek, Martyna; Jaroszyński, Andrzej (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Heading objectives: Granulomatosis with polyangiitis (GPA) is an antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) that may involve any organ. Rarely, clinical manifestation of inflammatory changes may resemble tumours, which, combined with untypical ovarian localization, may cause misdiagnosis and treatment delay. Case report: In this paper, we present the case of ovarian tumour-like lesion being the first manifestation of GPA and mimicking ovarian cancer. Conclusion: In case of a patient presenting with a tumour of untypical features, differential diagnosis should include inflammatory processes, including vasculitis.